Prospek Pengembangan Agribisnis Jaje Begine pada Kelompok Pelaku Usaha UP3HP Jempiring di Desa Blahkiuh, Abiansemal Badung - Astiti, Ni Wayan Sri; Suyathi, Ni Wayan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2016)
Badung regency in addition to having the potential of tourism development which is already known to the world also has the potential in the agricultural sector, which is the potential to develop agricultural product processing business of the sticky rice into jajan begina. There are round and rectangular jajan begina; generally, it is made between 7-12 cm diameters with red circle on the middle. Jaje begina is always used by Hindu people in every ceremony or religious activitiy for the offering, which believed to having the yang diyakini memiliki philosophical meaning of the universe-respect. The business development of jajan begina is held by PKK women by forming a business group which is “Jempiring” group, located in Banjar Tengah, Blahkiuh village, Abiansemal district, Badung regency with the membership of 18. Average business revenue in 2015 from January to June amounted Rp 198.646.000,00. Agribusiness Development Prospect of Jajan Begine seen from the ratio of profitability during the month of March 2015 has good prospects in which the ability to make a profit of 73.92%. The ability to repay the debt, short term and long term, is highly liquid in the amount of 3.160%. It shows that the agribusiness which is developed by the member of “Jempiring” business group of UP3HP is highly potential to be developed.
Keywords: Agribusiness, jajan begina, prospect